Comparison of different methods for work accidents investigation in hospitals: A Portuguese case study - Nunes, Cláudia (2015)
BACKGROUND: The hospital environment has many occupational health risks that predispose healthcare workers to various kinds of work accidents. OBJECTIVE: This study aims to compare different methods for work accidents investigation and to verify their suitability in hospital environment. METHODS: For this purpose, we selected three types of accidents that were related with needle stick, worker fall and inadequate effort/movement during the mobilization of patients. A total of thirty accidents were analysed with six different work accidents investigation methods. RESULTS: The results showed that organizational factors were the group of causes which had the greatest impact in the three types of work accidents. CONCLUSIONS: The methods selected to be compared in this paper are applicable and appropriate for the work accidents investigation in hospitals. However, the Registration, Research and Analysis of Work Accidents method (RIAAT) showed to be an optimal technique to use in this context.